Structural sediment connectivity dynamics in a representative watershed of the southern China’s red soil region: Response to land use/cover changes - He Wang; Songyang Li; Juan Wu; Huiguang Li; Yue Zhang; Fangshi Jiang; Yanhe Huang; Jinshi Lin (Journal of Hydrology: Regional Studies)
Study region: Red soil region of southern China Study focus: Land use/cover changes significantly affect the ecosystem’s potential for sediment detachment and transport capacity. These impacts can be manifested through variations in sediment connectivity, which reflects the continuity and strength of runoff and sediment pathways at a given point in time. Combining the sediment connectivity index (IC) with observed sediment data, this study assessed the dynamics of structural sediment connectivity and its response to land use/cover changes in a representative watershed of southern China's red soil region. New hydrological insight for the region: Over four decades of soil erosion control, land use and landscape patterns have changed minimally, but the vegetation cover has increased significantly. The mean IC values were −0.88, −0.87 and −3.77 in 1986, 2000 and 2019, respectively, indicating a great decrease in structural sediment connectivity. Croplands and highly fragmented landscape patterns can lead to high IC values. The changes in vegetation cover were the direct cause of IC reduction, which resulted in temporal variations in structural sediment connectivity. These variations aligned chronologically with regional development patterns and policies. Sediment connectivity changes became the main factor controlling sediment yield in the watershed from 2001 to 2020, reducing it by 57.56 % compared to 1982–1995 period. These findings provide spatial guidance for optimizing landscape patterns and cropland management to mitigate sediment connectivity hotspots in red soil regions.